Digital Activism: The Utilisation of Social Media Instagram @pulihkanjakarta in Campaigning for Environmental Issues - Isnata, Dita; Nugroho, Catur (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2024)
Abstract Environmental issues have become one of the most pressing global challenges over the past decade. Recognising the tremendous development of digitalisation today, WALHI Jakarta also uses new media in campaigning for environmental issues that arise, especially in the DKI Jakarta area. With the background mentioned above, the purpose of this research is to find out how WALHI Jakarta's communication strategy in campaigning environmental issues, how WALHI Jakarta uses social media in campaigning environmental issues and digital activism carried out by WALHI Jakarta in campaigning environmental issues. WALHI Jakarta campaigns on environmental issues through fact-finding, planning, action implementation and evaluation. Through Instagram @pulihkanjakarta, they spread fast and diverse information, involve affected communities, and combine physical action with digital technology. This research is also expected to be a scientific literature in future research related to organisational communication strategies, especially in the use of Instagram social media.